Curse of the Night Witch - Aster, Alex (2020)
After changing the fate he has known since birth, twelve-year-old Tor Luna, accompanied by his friends Engle and Melda, must visit the notorious Night Witch to break the curse he now faces.
Ages 8-14.
Grades 4-6.
Keywords: Fate and fatalism -- Fiction; Blessing and cursing -- Fiction; Quests (Expeditions) -- Fiction; Witches -- Fiction; Fantasy